Knowledge exchange between practitioners for the purpose of co-creating nature-based solutions - Borjana Bogatinoska; Angelique Lansu; Stefan C. Dekker; Jean Hugé; Jetse Stoorvogel (Ecosystems and People)
The planning and implementation of nature-based solutions require effective knowledge exchange among practitioners across multiple catchments. This study aims to enhance this knowledge exchange by applying a knowledge transfer model based on socialization, externalization, combination and internalization (SECI). The objective is to assess the effectiveness of this model in facilitating stakeholder engagement and co-creation approaches in the context of increasing hydro-meteorological hazards. To achieve this, we applied the SECI model across eight brook catchments in Belgium, the Netherlands, France and the United Kingdom. The study involved deploying various knowledge exchange instruments, which were then evaluated for their impact on fostering collaboration among a diverse range of stakeholders, including landowners, non-governmental organizations, local communities and other key beneficiaries of nature-based solutions. The results demonstrate that the structured application of the SECI model significantly enhances stakeholder collaboration and supports the co-creation of resilient water management practices. We highlight the outcomes from selected knowledge exchange instruments and discuss their potential to increase the uptake of co-creation approaches in planning nature-based solutions. Finally, the study identifies key challenges and barriers encountered in the co-creation process and offers insights into overcoming them for broader application in social-ecological contexts.